SEMANTIC ANALYSIS OF CONSTRAINTS, STATES AND ABSOLUTE MASDARS - SHIRIN ZAYNUTDINOVA (TADQIQOTLAR.UZ, 2024)
It consists of a set of words or some (some) of grammatically formed, intonational completeness, expressing relative conclusions. The concept of slices applies to sentences containing more than one word. It is not possible to speak of parts of a sentence in a single word. Because the parts of the sentence are part of the syntactic integrity that results from the interconnectedness of the words in the sentence.